Analysis of The Impact of Gadgets on Student Motivation and Learning: Reviewed After Covid - Fadlilah, Nur; Merlina, Shelli; Yuliza, Isma (International Journal of Education and Teaching Zone, 2023)
This research aims to determine student motivation and learning outcomes after the passing of Covid-19. The type of research that researchers use is qualitative. The research subjects used were in 2 classes, namely VIa and VIb. the number of VIa students is 23 people and VIb 22 students, and the number of students from both classes is 45 people. The data analysis techniques used were questionnaires and interviews. The samples used using the saturated model were VIa and VIb, with a total sample of 45 students. Analysis of the questionnaire that we distributed to students obtained the following results: on average students who were motivated by gadgets were 30% and those who were not motivated were 15% and, student learning outcomes were 31% and those who were less motivated were 14%.